Source apportionment of urban contaminants - Usman, Abida (2019)
Urban soils are major recipients of large amount of contaminants from multiple sources of both natural and anthropogenic origins. Accumulation of heavy metals at trace levels can be hazardous to human health and to the environment due to their ubiquity, high toxicity and persistent bioavailability. In order to mitigate the adverse effects of contaminants in soil, it is essential to have a better understanding of their characteristics and sources. Knowledge of contaminant sources is a prerequisite for developing appropriate prevention and control regulations. The overall aim of this research work was to undertake a forensic analysis of urban soil contaminants. The methodology included determination of Pb isotopic ratios in combination with a spectrum of associated elements. The experimental objectives utilized a sequential extraction procedure (SEP) and isotopic dilution (ID) to assess the fractionation and reactivity of pollutants and thereby reveal source-associations. A key part of the project was to refine experimental and instrumental protocols for accurate and precise measurement of Pb isotope ratios using a current generation inductively coupled plasma quadrupole based mass spectrometer (ICP-QMS). This is a widely available and relatively inexpensive instrument providing a rapid assay of isotope ratios. However, ICP-QMS is subject to various interferences which limit the accuracy and precision of Pb isotope signals. The protocol developed on the ICP-QMS benchmarked very well against multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS) assays on the same sample material. The protocol was then applied to a range of samples, including soils from urban locations, sewage-amended arable fields and allotments, in order to determine soil Pb source apportionment. The characterization of Pb isotopes were helpful in confirming that Pb from petrol and local geological (coal, ore) sources were the dominant sources of Pb in soils. The examination of Pb isotopic ratios in allotment topsoils and subsoils was useful in revealing the extent to which labile Pbpetrol migrated down the soil profile into the subsoils. The evaluation of trends of Pbpetrol with total soil Pb (Pbtotal) further helped in identifying allotment sites where the main influence was from vehicular emissions and coal burning. The determination of Pb isotopes in the individual fractions of SEP was a useful approach in giving more insight regarding the estimation of Pbpetrol and Pbgeogenic associated with different phases. The relative proportion (%) of Pbgeogenic in all fractions was greater (>67%) than the Pbpetrol whereas highest proportion Pbpetrol was observed associated with the most labile fraction (F1). Measurement of Pb isotopes also helped in assessing the behaviour of Pbpetrol across different fractions of SEP. An interesting finding was the presence of Pbpetrol (24%) in the most resistant fraction (F5), which was unexpected. The proportion of Pbpetrol in F5 was greatest in soils with greater concentration of organic matter, available P and Pbtotal. This may represent transformation of initially soluble Pbpetrol to more resistant forms through reaction with soil constituents or, it might be an artefact arising from resistant anthropogenic (non-petrol) Pb that does not have a typical isotopic signature of ‘geogenic Pb’. The measurement of labile (isotopically exchangeable) trace metals including Ni, Cu, Cd, Zn and Pb in allotment soils showed that the reactivity of these five trace metals were below 50% and followed a consistent decreasing order of Cd> Pb≥ Zn> Cu> Ni. The overall weak influence of soil properties on lability of trace metals suggested a lasting impact from the original contaminant sources. Furthermore, the relative contribution of Pbgeogenic (coal Pb) to both labile and non-labile fractions was greater whereas surprisingly the intrinsic lability of Pbpetrol was observed lower. The greater lability of Pbgeogenic was unexpected which reflected that the particulate coal-derived Pb arrived as aerial deposition were in more reactive form. The comparison of E-values for Ni, Cu, Zn, Cd and Pb with SEP data showed no consistent agreement between the labile fractions and any single fraction although a reasonable correspondence was found between metals extracted in combined fractions (i.e., F1+F2) and E-values for Zn and Ni. In case of Cu, the non-isotopically exchangeable fraction correlated with the sum of the most resistant two fractions (i.e., F4+F5). Approach such as cluster analysis (dendrogram) using the full range of trace elements with source apportioned Pb (Pbpetrol and Pbgeogenic) in all sets of soils (urban soils, sewage amended soils and allotment soils) was to some extent helpful in understanding the likely origins of key contaminant metals and metalloids. In allotments, the variation observed in the concentration of trace metals at different sites was partly associated with the location, age and history of sites. For example, site BH, relatively new allotment and remote was less contaminated compared to other allotments which were near to major pollutant sources. Forensic analysis of trace elements including REEs and PGEs in allotment soils was of limited use in identifying other specific sources of contaminants. It revealed that REEs mainly originated from natural sources whereas, the EFs values and comparison of isotopic abundance ratios with the mean upper continental crust (UCC) showed a small influence from anthropogenic sources such as fertilizers. The concentration of PGEs were below detection limit following sample preparation. This revealed two possibilities, first there was no substantial influence of PGEs on allotment soils. Secondly the method used for soil digestion and resulting dilutions would have produced solution with very low concentrations of PGEs. An optimised analytical approach (e.g. digestion of samples with Aqua regia and pre-concentration) is therefore suggested for determination of PGEs in soils.